(3eSGFd eLehYI ef cdGe GdEeGe GdefUhQ HGddg aj Mb GdUMGHI GdPjf JbOehG Ydi Hf CHj WGdHs ((3MSf Hf eMeO Hf eMQe GdTQbi s)
(3ChdgG (B:s
(3bGd GdSGFd , eSGdI ai GdUMGHI GdPjf JbOehG Ydi hef JHYge hHGjYge s
(3BNQgG (B:s
(3aCNPgG GdfUQGfi HXGgQ GdTQjYI , hYdi Chdi HgG ai Ydeg , agPG dGeYhd Ydjg dPi eYQaI , Je Pdc s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdJhMjO hGdedd hGdfMds